The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/cncr.29097
|View full text |Cite
|
Sign up to set email alerts
|

The symptom burden of treatment‐naive patients with head and neck cancer

Abstract: Background Treatment for head and neck cancer (HNC) may cause substantial local and systemic symptomatic morbidities, but many patients have high symptom levels before treatment begins. Knowledge of disease-related (treatment-naive) symptom status would aid evaluation of the symptomatic benefit or burden of HNC therapies. Methods We retrospectively examined symptoms, quality of life, and health status reported by HNC patients who were naïve to any treatment. We explored symptoms by anatomical site and correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…A recent study found that HNC patients with lymph node metastases were more likely to report severe pretreatment pain compared to patients without lymph node involvement, and that this was significantly correlated with measures of overall quality of life and increased symptom burden. 4 Pre-treatment pain has been associated with poorer overall survival in patients with HNSCC 18 thus suggesting the need for prompt pain treatment and management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that HNC patients with lymph node metastases were more likely to report severe pretreatment pain compared to patients without lymph node involvement, and that this was significantly correlated with measures of overall quality of life and increased symptom burden. 4 Pre-treatment pain has been associated with poorer overall survival in patients with HNSCC 18 thus suggesting the need for prompt pain treatment and management.…”
Section: Discussionmentioning
confidence: 99%
“…10 This study identifies gastrointestinal symptoms as the primary reason for emergency department presentation and one of the primary discharge diagnoses in this population, consistent with known symptoms of head and neck cancer treatment. 4,11,12 Dysphagia (impairment of the swallowing process) is common in patients with HNSCC, and is often underdiagnosed and improperly treated, 13 resulting in dehydration and malnutrition 14 and may necessitate the use of nonoral nutritional support. A recent study aimed at understanding the management and prevention of acute and late effects because of head and neck cancer therapy, in particular, treatment associated effects related to swallowing, suggested that precautions can be taken before, during, and after treatment in order to minimize the impact of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined the symptom burden as the number of severe symptoms rated as 7 on the MDASI's 0 to 10 scale on the basis of results from various studies. 18,20…”
Section: Symptom Burdenmentioning
confidence: 99%
“…Commonly, head and neck tumors produce many symptoms and disturbances in patients. In a recent study with 748 head and neck cancer patients, Hanna et al 1 demonstrated that more than 30% of treatment-na€ ıve patients reported moderate to severe symptoms related to sleep disturbances, distress, and fatigue. Gunn et al 2 also demonstrated that specific symptoms related to tasting, swallowing, speech, and mucus in the throat can increase in frequency by three-to seven-fold after treatment.…”
Section: Introductionmentioning
confidence: 99%